Severe Ovarian Hyperstimulation Syndrome in a Woman With Breast Cancer Under Letrozole Triggered With GnRH Agonist: A Case Report and Review of the Literature - Iorio, Giuseppe Gabriele; Rovetto, Marika Ylenia; Conforti, Alessandro; Carbone, Luigi; Vallone, Roberta; Cariati, Federica; Bagnulo, Francesca; Di Girolamo, Raffaella; La Marca, Antonio; Alviggi, Carlo (Frontiers in Reproductive Health, 2021)
We report a rare case of ovarian hyperstimulation syndrome (OHSS) in a 28-year-old woman with breast cancer and with a history of polycystic ovary syndrome (PCOS) despite treatment with letrozole and gonadotropin-releasing hormone agonist (GnRH-a) triggering in a GnRH antagonist (GnRH-ant) protocol without the administration of any human chorionic gonadotropin (hCG) for luteal-phase support. The patient, who underwent controlled ovarian syndrome (COS)-oocyte cryopreservation before chemotherapy, required hospitalization. Complete recovery was achieved after treatment with volume expanders, human albumin, and cabergoline. Based on our case and literature review, it is possible to establish that estradiol (E2) modulation with letrozole and GnRH-a triggering does not eliminate the risk of OHSS. Furthermore, it is advisable to postpone GnRH-a depot to minimize the risk of OHSS after the suspension of letrozole, following menstruation or at least 7–8 days after triggering. It would be desirable to identify high-risk patients, also on a genetic basis, in order to avoid delays in oncologic treatments that could strongly impact life expectancy.